Anatomical Variants, Pneumatization Classification, and Volumetric Studies of the Sphenoid Sinus With High-Resolution Computed Tomography. Issue 7 (October 2021) - Yan, Yujia; Guo, Fang; Liu, Jiayu; Yu, Meng; Huang, Ying
Abstract : Objectives: Aimed to explore the correlation between the volume of the sphenoid sinuses (SS) and sex, age, pneumatization and its anatomical variant types. Material and Methods: Retrospectively evaluated high-resolution computed tomography images of 170 individuals; were studied by ITK-SNAP software to measure the volume of SS. Results: The average volume of SS was a significant difference between the gender, the volume of SS in the elderly group (≥65 years old) showed a downward trend. The volume of the SS in the variants of the anterior clinoid processes, pterygoid processes, greater wings, and clivus were significantly higher than in the nonvariants ( P < 0.05). With the expansion of pneumatization, the optic nerve (CNII) type 3-4, the internal carotid artery (ICA) type 2-3 and the septal insertion on the ICA have a larger volume, while the occurrence of septal insertion on only the CNII was not correlated with the volume ( P > 0.05). Conclusions and Significance: The volume of SS is closely related to age, sex, the type of pneumatization and anatomical variation. High-resolution computed tomography can facilitate a precise study of anatomical variations and adjacent structures and help ensure the safety of an operation. Abstract : Supplemental Digital Content is available in the text